Excavaciones en el baptisterio del conjunto eclesiástico de Son Peretó (Manacor, Mallorca, islas Baleares) : siglos V-VIII D.C. - Riera Rullan, Mateu,; Cau Ontiveros, Miguel Angel,; Salas Burguera, Magdalena, (Limina/limites., 2021)
Presents the results obtained in the archaeological excavations of the baptistery of the Late Antique site of Son Peretó (Manacor), located on the island of Mallorca in the Balearic Islands (Spain). The volume offers a review of what has been published on the baptismal space in the 20th century and provides some unpublished data on the discoveries made during that time. The focus of the monograph, however, is to present the results of excavations carried out between 2005 and 2016 and on the study of the movable and immovable finds made within the framework of the current research project on this site.